Analysis of Environmental Factors, Children's Eating Patterns and Access to Health Services on the Incidence of Malnutrition - Agus Heselo; Indasah; Joko Prasetyo (Universitas STRADA Indonesia, 2025)
Malnutrition in children is a serious and persistent health problem in many rural areas. Environmental conditions, diet, and access to health services were relevant factors. This study aims to analyze the influence of these three factors on the incidence of malnutrition among school-age children. This cross-sectional study was conducted in December 2023 on 168 school-aged children in Kurima District, Yahukimo Regency. Simple random sampling was used. Data was collected using a questionnaire and analysed using regression. Environment (p=0.003), diet (p=0.008), and access to health services (p=0.027) had a significant influence on the incidence of malnutrition in school-age children both partially and simultaneously (p=0.000). Environmental factors, diet, and access to health services were able to predict 54.5% of school-age child malnutrition variables. Health professionals should consider these factors in solving malnutrition problems.